Achievement of Value Markers of the Harmonious Development of Agrarian Territories in the Volga Federal District in the Context of Russia’s National Security - YASHKIN, Alexey Vladimirovich; ZINCHUK, Galina Mikhailovna; ILYINA, Alena Igorevna; BALANDINA, Svetlana Vladimirovna (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022, 2022)
The article presents the results of a sociological survey, which investigated the level of achievement of the harmonious development of agrarian territories of the Volga Federal District of Russia. The survey of representatives of agricultural territories (farmers, rural residents engaged in wage labor, representatives of the scientific community, and municipal authorities) was conducted based on 15 indicators, which included social, economic, and environmental factors affecting the satisfaction of the population with the activities of state and municipal authorities. The choice of factors was based on the value orientations and attitudes enshrined in the current strategy, as well as the state strategies for ensuring the national security of Russia that have lost their legal significance, but not relevance. To determine the level of achievement of value markers, 110 respondents were asked questions assessing the importance of a particular indicator and the respondent's satisfaction with the undertaken actions of state and municipal authorities corresponding to this indicator. For objectivity, in particular cases, groups of respondents were assigned weighting coefficients, whose purpose was smoothing the biased attitude. As a result of the study, eight value markers were identified in which the gap between the importance and satisfaction of respondents was the largest, i.e. problem areas were identified. Comparison of the identified problem areas with the current regulatory legal acts allowed formulating proposals to improve the quality of management of agrarian territories of the Volga Federal District.